Effect of stimulator of interferon genes (STING) signaling on radiation-induced chemokine expression in human osteosarcoma cells. - Sita S Withers; Cambri E Moeller; Cally N Quick; Chin-Chi Liu; Shelby M Baham; Jayme S Looper; Ramesh Subramanian; Konstantin G Kousoulas (PLoS ONE, 2023)
Cancer cell-intrinsic mechanisms affecting radiation immunomodulation could be exploited to optimize systemic effects of localized radiation. Radiation-induced DNA damage is sensed by cyclic GMP-AMP synthase (cGAS), which ultimately activates stimulator of interferon (IFN) genes (STING). Resultant expression of soluble mediators such as CCL5 and CXCL10 can facilitate recruitment of dendritic cells and immune effector cells into the tumor. The primary objectives of this study were to determine the baseline expression levels of cGAS and STING in OSA cells and evaluate the dependence of OSA cells on STING signaling for eliciting radiation-induced expression of CCL5 and CXCL10. cGAS and STING expression, and CCL5/CXCL10 expression in control cells, STING-agonist treated cells, and cells treated with 5 Gy ionizing radiation were assessed utilizing RTqPCR, Western blot, and ELISA. U2OS and SAOS-2 OSA cells were deficient in STING relative to human osteoblasts (hObs), while SAOS-2-LM6 and MG63 OSA cells expressed equivalent amounts of STING compared to hObs. A dependence on baseline or induced STING expression was observed for STING-agonist, and radiation-induced, expression of CCL5 and CXCL10. This finding was confirmed by performing siRNA knockdown of STING in MG63 cells. These results show that STING signaling is necessary for radiation-induced expression of CCL5 and CXCL10 in OSA cells. Additional studies are necessary to determine whether STING expression in OSA cells in vivo alters immune cell infiltrates after radiation exposure. These data may also have implications for other potentially STING-dependent characteristics such as resistance to oncolytic virus cytotoxicity.